An extracellular miRNA reshapes cell wall integrity to prime systemic immunity in tomato - Yue Qiao; Yu Xia; Jianfei Shi; Zihan Song; Liying Jin; Lijie Xuan; Haolin Yang; Xiang Yu; Ruoshi Wang; Haiyan Liu; Ali Zhang; Jinfeng Chen; et al. (Molecular Plant, 2026)

A composite ecological drought index integrating multi-source water and heat stress with time-lag effects: Insights from the Yellow River Basin - Jingtian Ma; Lianqing Xue; Yuanhong Liu; Saihua Liu; Ruoshi Xu (Journal of Environmental Management, 2026)

Long-term water quality monitoring and assessment in lakes along large-scale water diversion project: An ensemble machine-learning approach using Graph Convolutional Network and Random Forest - Ruoshi Xu; Lianqing Xue; Yuanhong Liu; Saihua Liu; Jingtian Ma; Wujie Zhou (Journal of Water Process Engineering, 2026)

Tree-ring δ18O, a window into the summer hydroclimatic variations in the Central Water Tower of China - Qiufang Cai; Hanyu Zhang; Yu Liu; Mei Xie; Meng Ren; Qiang Li; Changfeng Sun; Huiming Song; Ruoshi Liu; Kebayier Meng; Dan Chen (Journal of Hydrology, 2026)

Enhanced biosynthesis of 6-aminocaproic acid in engineered Escherichia coli with artificial protein cage-organized enzymatic cascades - Ruoshi Luo; Lin Hu; Dan Wang; Kaixing Xiao; Xuemei Liu; Yaqi Kang; Qinhong Wang (Bioresource Technology, 2025)

Mineralization preparation of PVDF@TA/MnO2 nanofiber membrane for efficient oil-water separation and dye degradation - Ruoshi Zhang; Jiuyun Cui; Hailong Wang; Qihang Liu; Can Wei; Jirong Luo; Atian Xie (Journal of Environmental Chemical Engineering, 2025)

Winter Dormant Wheat Will Benefit From Mean Temperature Increase of 2°C When Well‐Watered and Fertilized in the Main Producing Regions of China - Ruoshi Wang; Chuang Zhao; Senthold Asseng; Bing Liu; Alex C. Ruane; Jiahui Cong; Xi Wang; Zhijuan Liu; Jin Zhao; Xiaoguang Yang (Global Change Biology, 2025)
Rising temperatures are projected to lead to a decline in global wheat production. However, this global trend belies the regional nuances of this impact, such as observed local yield increases in some field experiments in the winter wheat‐growing region of China. This study combines detailed data from eight field warming experiments and outputs of simulation by an ensemble of three point‐based crop models and an ensemble of 10 global gridded crop models to scrutinize the influence of warming on winter wheat yield in the main producing regions of China (MPC). Observed data were obtained from published reports of field experiments, where winter wheat was grown with sufficient water and nitrogen under free‐air‐temperature increase (FATI) by 2°C. Growth and physiology of winter wheat in the field experiments were simulated by three point‐based crop models to validate the effects of warming on wheat growth and yield as simulated by grid‐based crop models. Results of field observations and grid simulations both indicate notable increases in average grain yield (observed +13%, simulated +8%) and aboveground biomass (observed +15%, simulated +7%) under 2°C warming across the MPC. The winter dormancy and pre‐anthesis duration were shorter with warmer temperature, with the effect that the grain filling period between anthesis to maturity was extended by 6 days. The shorter phenology affected wheat photosynthesis because less solar radiation was available (−6%) over the growth period. However, the leaf area index started to develop earlier and reached a higher maximum than un‐warmed control, so the cumulative solar radiation for photosynthesis intercepted by warmed wheat was higher (+9%), as well as the radiation use efficiency (+1%). These findings suggest that well‐irrigated and well‐fertilized winter dormant wheat is likely to experience yield gains with local warming of up to 2°C, bolstering confidence in future adaptation of wheat production in China.

Low-damage fetching method for pepper seedlings based on Res-Unet - Xin Jin; Shuang Chen; Lijun Zhao; Ruoshi Li; Qing Li; Song Gu; Guowei Liu; Jiangtao Ji (Computers and Electronics in Agriculture, 2024)

Human activities have more impacts on the recent discharge reduction of the largest tributary of the Yellow River relative to last three centuries - Changfeng Sun; Qiang Li; Yu Liu; Qiufang Cai; Meng Ren; Huiming Song; Congxi Fang; Ruoshi Liu; Junyan Sun (Science of The Total Environment, 2023)

Sensitive climate response of tree-ring δ18O to current warming in the Qinling Mountains along a climate boundary in China - Qiang Li; Yu Liu; Huiming Song; Ruoshi Liu; Qiufang Cai; Changfeng Sun; Congxi Fang; Hai Cheng (Climate Dynamics, 2023)

Indian summer monsoon and winter Total Solar Irradiance signals in the tree‐ring δ 18 O from foothills of High Asia, northern Pakistan - Qiang Li; Yu Liu; Ashish Sinha; Gayatri Kathayat; Xiangyu Duan; Ruoshi Liu; Chenxi Xu; Huiming Song; Congxi Fang; Muhammad Faheem Siddiqui; Hai Cheng (International Journal of Climatology, 2023)
A tree‐ring stable oxygen isotope (δ 18 O) chronology was developed for the past 171 years by four Abies pindrow trees growing in southwest foothills of High Asia, northern Pakistan, which is correlated with observed and modelled δ 18 O of precipitation in Islamabad over the instrumental period. The averaged tree‐ring δ 18 O chronology is significantly negative correlated with local ( r = −.651, p n = 38) and regional ( r = −.664, p n = 65) summer precipitation variations. Analysis of vertically integrated water vapour flux and surface wind field suggests that the sampling site is located at the northern limit of the Indian summer monsoon (ISM). Our tree‐ring δ 18 O series is significantly ( p n = 143) negatively correlated with observed Homogenous India rainfall, All Indian rainfall, Core‐Monsoon India rainfall and Northwest India rainfall. This is the first detected ISM signal from tree‐ring δ 18 O over northern Pakistan. Several ISM‐related paleoclimate proxies, including three stalagmites δ 18 O series (Sahiya cave, Jhumar cave and Qunf cave) and a tree‐ring δ 18 O series (Manali), show consistent variability and a correlation coefficient of .566 ( p n = 165) with our tree‐ring δ 18 O, suggesting that a combination of multiple proxies may be potentially useful to understand the full perspective of ISM before instrumental era. In addition, we found that the satellite‐observed winter Total Solar Irradiance exerts influence on the tree‐ring δ 18 O variation ( r = .643, p n = 38), which may be linked to runoff of the Indus River and ISM precipitation.

Kainic acid induced hyperexcitability in thalamic reticular nucleus that initiates an inflammatory response through the HMGB1/TLR4 pathway - Dongbin Li; Xiaosi Zhang; Ruoshi Liu; Meixin Long; Shanshan Zhou; Jinghan Lin; Liming Zhang (NeuroToxicology, 2023)

Quality of chicken breast meat improved by dietary pterostilbene referring to up-regulated antioxidant capacity and enhanced protein structure - Yingjie Wang; Xin Zhou; Mengru Liu; Haoran Zang; Ruoshi Zhang; Hao Yang; Sanjun Jin; Xueyan Qi; Anshan Shan; Xingjun Feng (Food Chemistry, 2023)

Theoretical System of Sandstone-Type Uranium Deposits in Northern China - Ruoshi Jin; Huajian Liu; Xiaoguang Li (Journal of Earth Science, 2022)

Recent intensification of hydroclimatic change in the middle reaches of the Yangtz River Basin driven by PDO, ENSO and WPSH - Qiufang Cai; Hengjun Qian; Yu Liu; Congxi Fang; Hanyu Zhang; Qiang Li; Changfeng Sun; Huiming Song; Ruoshi Liu; Junyan Sun (Climate Dynamics, 2022)

Relative humidity variation derived from tree‐ring δ 18 O and possible large‐scale atmospheric circulations linkage over the Guanzhong Plain, central northern China, since 1760 CE - Ruoshi Liu; Qiang Li; Yu Liu; Xuxiang Li; Meng Ren; Yongyong Ma; Changfeng Sun; Huiming Song; Qiufang Cai (International Journal of Climatology, 2021)
China is drastically influenced by the Asian monsoon. Based on the relationship ( r = −.636, N = 62, p 18 O values from nine cores of Pinus tabulaeformis Carr. from Nanwutai and the Asia monsoon‐related June–August relative humidity (RH JJA ), we designed a transfer function reconstructing the RH JJA variation from 1760 to 2018 CE. Our RH JJA reconstruction captured some extreme climatic events that occurred in the past, such as the Ding‐Wu disaster (1876–1878 CE), which was the most serious drought event of northern China in the 19th century, and the severe drought event of 1925–1930 CE. The spatial correlation analysis shows that our RH JJA reconstruction has not only local but also large‐scale hydroclimate circulations. Our reconstruction compared well with other hydroclimate series from northern China, indicating the large‐scale representativeness of our reconstruction. Both the ensemble empirical mode decomposition (EEMD) and the periodicity analyses revealed that the El Niño–South Oscillation (ENSO), the Pacific Decadal Oscillation (PDO), the Arctic Oscillation (AO) and the solar activity strongly affected Asian monsoon‐related RH JJA changes over Guanzhong Plain in the past. We believe this study is of great significance and provides an in‐depth understanding of climate change in the Guanzhong Plain and in northern China.

Maximum July–September temperatures derived from tree‐ring densities on the western Loess Plateau, China - Huiming Song; Ruochen Mei; Yu Liu; Daniel Nievergelt; Anne Verstege; Paolo Cherubini; Ruoshi Liu; Changfeng Sun; Qiang Li; Ling Chen; Xueli Zeng; Junqin Guo (International Journal of Climatology, 2021)
Tree‐ring densitometric studies conducted in semi‐arid regions are exceedingly rare. In this study, we evaluate a new maximum latewood density chronology from a collection of Picea purpurea trees growing in semi‐arid northwestern China for climatic reconstruction purposes. We find statistically significant correlations between annual maximum density variations and July–September maximum temperatures over the 1957–2014 calibration period. Using a linear model to transfer the density variations to temperature estimates, we then reconstruct maximum summer temperatures from 1840 to 2014. Statistical analyses and verification tests demonstrate that the resulting transfer function is both reliable and stable. The reconstructed temperature series shows strong inter‐annual and decadal variability. Several extremely cool and warm years are apparent on an inter‐annual scale, while three extended cool periods and a warm period are observed on a decadal scale. In addition, the reconstructed temperature series exhibits a pattern synchronous with that of the Indian monsoon index, as well as a moderate relationship to volcanic eruptions. This densitometric study reveals typical climatic variation characteristics and provides useful data for deepening our understanding of climate history in the semi‐arid regions of China.

Similarities and differences in driving factors of precipitation changes on the western Loess Plateau and the northeastern Tibetan Plateau at different timescales - Changfeng Sun; Yu Liu; Qiufang Cai; Qiang Li; Huiming Song; Congxi Fang; Ruoshi Liu (Climate Dynamics, 2020)

Temperature variation at the low‐latitude regions of East Asia recorded by tree rings during the past six centuries - Yu Liu; Ching‐Yao Li; Changfeng Sun; Huiming Song; Qiang Li; Qiufang Cai; Ruoshi Liu (International Journal of Climatology, 2020)
The understanding of past millennium climate change is very important. Due to the lack of continuously annual resolution records, the temperature characteristics in the low‐latitude regions of East Asia (LLREA) during past several centuries are still unknown. Using tree‐ring width chronology from Taiwan, an island located in the western Pacific region and in southeastern China, February–October mean temperature from 1380 to 2007 AD was reconstructed. Spatial correlation analysis indicated that the reconstructed temperature could represent the sea‐land temperature change in LLREA. During the past six centuries, both the warmest intervals and the largest variability of temperature appeared in the twentieth century. This is probably related to human activities. Temperature in LLREA provided good contrast with temperature changes in the Tibet Plateau and elsewhere in the Northern Hemisphere. The LLREA entered into the Little Ice Age around the year of 1450, approximately 100 years earlier than the Tibet Plateau. The 10‐year cycle contained in the reconstructed temperature is close to the 11‐year period of solar activity, which revealed there was a certain relationship between them. The temperature in LLREA significantly correlated with solar activity at the decadal to centennial scales. The strong/weak solar irradiance corresponded to the great/small temperature variability.

Seasonal Palmer drought severity index reconstruction using tree-ring widths from multiple sites over the central-western Da Hinggan Mountains, China since 1825 AD - Ruoshi Liu; Yu Liu; Qiang Li; Huiming Song; Xuxiang Li; Changfeng Sun; Qiufang Cai; Yi Song (Climate Dynamics, 2019)

East Asian Summer Monsoon moisture sustains summer relative humidity in the southwestern Gobi Desert, China: evidence from δ18O of tree rings - Qiang Li; Yu Liu; Takeshi Nakatsuka; Keyan Fang; Huiming Song; Ruoshi Liu; Changfeng Sun; Gang Li; Ke Wang (Climate Dynamics, 2019)

Covalently mucoadhesive amphiphilic prodrug of 5-fluorouracil for enhanced permeation and improved oral absorption - Yan Liu; Dongyang Zhao; Mengchi Sun; Wei Wei; Yingli Wang; Jiahua Zhou; Ruoshi Zhang; Jian Wang; Haotian Zhang; Zhonggui He; Qiming Kan; Jin Sun (Drug Delivery and Translational Research, 2018)

Tree‐ring‐based precipitation reconstruction in the source region of Weihe River, northwest China since AD 1810 - Changfeng Sun; Yu Liu; Huiming Song; Ruochen Mei; Paramate Payomrat; Lu Wang; Ruoshi Liu (International Journal of Climatology, 2018)
A tree‐ring width chronology of Picea purpurea Mast from Mt. Shouyang in the source region of Weihe River (SWR), northwest China, was developed in this study. Correlation analysis showed that the precipitation from previous August to current July was the limiting climate factor of tree growth. Using a reliable and stable linear regression model, which explained 42.6% of the variance of the actual precipitation during the calibration period from 1958 to 2014, a 205‐year long precipitation series was reconstructed for the SWR. The dry years in the reconstruction were well supported by historical documents, and famous historical droughts were also recorded in the dry periods of a low‐frequency scale of the reconstructed precipitation. As demonstrated by the spatial correlation patterns, the reconstructed series compared well with other hydroclimate records for northwest China, indicating that it could represent large‐scale hydroclimate changes. The 2–8‐year interannual cycles and the interdecadal quasiperiods of 15.9 years and 18.6 years revealed that the precipitation in this region was probably affected by the El Niño‐Southern Oscillation and North Atlantic Oscillation. The dry/wet years corresponded well with the El Niño/La Niña events and the SWR commonly experienced droughts during the low periods of North Atlantic Oscillation.